The real modern : literary modernism and the crisis of representation in colonial Korea - Hanscom, Christopher P., 1972- (Harvard East Asian monographs ;, 2013)
"Examines the critical and literary production of Pak T'aewon, Kim Yujong, and Yi T'aejun, whose works confront the "crisis of representation" from loss of faith in language as a vehicle of meaningful reference to the world. Bridging literary and colonial studies, this re-reading of modernist fiction within the imperial context illuminates links between literary practice and colonial discourse"--Provided by publisher